Preparation method of nano flame retardant and flame-retardant thermoplastic polyurethane composite material

By using nanofire retardants based on bimetallic selenide and modified boron nitride in TPU, the problem of flammability of TPU is solved, significantly improving its flame retardant performance and fire safety.

CN119431885AActive Publication Date: 2025-02-14NANJING TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411808309.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Thermoplastic polyurethane elastomer TPU is flammable and will quickly burn and decompose when exposed to fire to produce a large amount of toxic smoke, limiting its application in areas with high fire safety requirements.

Method used

Using nanofire retardants based on bimetallic selenide and modified boron nitride, bimetallic selenide is grown in situ on the surface of boron nitride through interface engineering strategies to form a multi-level flame retardant nanostructure, which significantly improves the resistance of the material. Fueling performance.

Benefits of technology

It significantly reduces the heat release rate, total heat release, and the generation rate and yield of toxic flue gas, and improves the fire safety of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431885A_ABST
    Figure CN119431885A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a nano flame retardant and flame-retardant thermoplastic polyurethane composite material, which comprises the following steps: placing modified boron nitride in deionized water, adding a buffer solution, weighing dopamine hydrochloride, and adding the dopamine hydrochloride into the mixed solution for reaction; after the reaction is finished, performing suction filtration to obtain a product, washing to be neutral, and drying to obtain P-coated BN; dispersing P-coated BN in deionized water, and adding a mixed metal salt to form a dispersion liquid II; meanwhile, selenium powder is taken and placed in a hydrazine hydrate solution, and a selenium solution is formed; adding a selenium solution into the dispersion liquid II, and carrying out hydrothermal reaction; and sequentially carrying out centrifugal collection, washing and drying on the initial product to obtain the nano flame retardant P-coated BN-BMSe. The preparation method comprises the following steps: putting a nano flame retardant P-coated BN-BMSe into an organic solvent, carrying out ultrasonic stirring, and adding thermoplastic polyurethane elastomer rubber to obtain a composite solution; and adding the composite solution into deionized water, separating out, drying, banburying, and pressing to obtain the flame-retardant thermoplastic polyurethane composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant composite materials, and in particular relates to a method for preparing a nano flame retardant and a flame retardant thermoplastic polyurethane composite material. Background Art

[0002] Thermoplastic polyurethane elastomer TPU is a type of elastic polyurethane that can be plasticized by heating. The molecular structure is a block linear polymer obtained by copolymerization of diisocyanate and polyol. There is no chemical crosslinking, but it has certain physical crosslinking characteristics at the use temperature. TPU has excellent wear resistance, aging resistance, high resilience, etc., and is widely used in industry, life, medical treatment, military industry and other aspects.

[0003] However, TPU is flammable, and its limiting oxygen index (LOI) is only 16%-18%. It will burn quickly and decompose to produce a large amount of toxic smoke when it encounters fire. This shortcoming also seriously affects the application of TPU in some fields with high fire safety requirements. Therefore, it is very important to modify the flame retardant of TPU materials.

[0004] For example, the patent CN202010623398.X has been published, a low-smoke thermoplastic polyurethane elastomer composite material and its preparation method, when the flame retardant addition amount is 2wt%, the peak value of the heat release rate increases, and the peak value of the smoke release rate decreases by 37.7%; the patent CN202010678113.2 has been published, a halogen-free flame-retardant thermoplastic polyurethane nanocomposite material and its preparation method, when 2wt% of the flame retardant is used, the peak value of the smoke release rate decreases by 43.8%; the patent CN201510686290.4 has been published, a montmorillonite composite flame retardant and its preparation method, when 3wt% of the flame retardant is added, the peak value of the heat release rate and the total amount of heat release decrease by 26.0% and 7.8% respectively. The above-mentioned composite materials disclosed in the prior art have reduced parameters such as heat release rate and smoke release rate, but still have a large room for improvement. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a nano flame retardant and a flame retardant thermoplastic polyurethane composite material. In view of the problem that TPU will burn rapidly and decompose to produce a large amount of toxic smoke when it encounters fire, the nano flame retardant provided by the present invention is prepared based on bimetallic selenide and modified boron nitride, and as a modified flame retardant of TPU material, it can reduce the heat release rate, total heat release and the generation rate and output of toxic smoke of TPU.

[0006] In order to solve the above technical problems, the present invention is implemented in the following manner: The preparation method of bimetallic selenide / modified boron nitride nano flame retardant comprises the following steps: Step 1: Place the modified boron nitride in deionized water and obtain a uniform dispersion solution 1 by ultrasonic treatment; take a buffer solution, add it to the dispersion solution 1, and then weigh dopamine hydrochloride and add it to the mixed solution for reaction; after the reaction is completed, filter to obtain the product, then wash it with deionized water until the pH is neutral, dry it and collect it to obtain P@BN; Step 2: P@BN is dispersed in deionized water, and then mixed metal salts are added and ultrasonically stirred to form dispersion liquid 2; at the same time, selenium powder is placed in a hydrazine hydrate solution and dissolved by magnetic stirring to form a selenium solution; the selenium solution is added to dispersion liquid 2, and ultrasonic stirring is continued before hydrothermal reaction; the initial product after the reaction is centrifuged, washed, and dried in sequence to obtain the final product, nano flame retardant P@BN-BMSe.

[0007] Further optimization, in step 1, the boron nitride and the modifier are placed in a high-energy ball mill for simultaneous stripping and modification to obtain modified boron nitride.

[0008] Boron nitride is a crystal composed of nitrogen atoms and boron atoms. Boron nitride has four different variants, each with a unique crystal structure. It has the characteristics of high thermal conductivity, high hardness, high chemical stability and excellent lubricity. Due to its excellent thermal conductivity and electrical insulation properties, it is often used as a high-temperature electronic packaging material such as chip carriers and heat sinks; in addition, due to its high corrosion resistance and high-temperature stability, it is often used as a high-corrosion-resistant material, release agent and lubricant. Boron nitride lacks surface functional groups and is very easy to form agglomerations in the polymer matrix, which is not conducive to performance improvement. Therefore, the present invention adopts an interface engineering strategy, adds a modifier and places it in a high-energy ball mill, performs synchronous stripping, obtains modified boron nitride, and significantly improves its dispersibility.

[0009] Further optimized, the boron nitride is one of hexagonal boron nitride (h-BN), rhombohedral boron nitride (r-BN), cubic boron nitride (c-BN) or wurtzite boron nitride (w-BN); The modifier is a mixture of one or more of urea, dicyandiamide, melamine and hexamethylenetetramine.

[0010] Further optimization, in step 2, the mass ratio of P@BN to the mixed metal salt is (1:3) to (1:10), and the mixed metal salt is composed of two metal salts, and the mass ratio of the two is 1:1.

[0011] Further optimization, in step 2, the dosage ratio of the P@BN, selenium powder and hydrazine hydrate is 1g: (1-5)g: (10-30)ml.

[0012] There are three chemical bonds in metal selenides: MM (metal-metal), M-Se (metal-selenium) and Se-Se (selenium-selenium). The formation of these chemical bonds makes metal selenides have a variety of crystal structures and exhibit unique physical and chemical properties. Some transition metal selenides have large specific surface area, high surface activity and excellent catalytic activity. Considering its lamellar structure and catalytic properties, the use of metal selenides as flame retardants improves the safety performance of materials and reduces the generation of smoke and harmful gases. The two metal elements in bimetallic selenides can produce synergistic catalysis, enhance the transfer of charges and improve catalytic activity. Bimetallic selenides usually also have high conductivity, which is conducive to the transfer of electrons and the progress of catalytic reactions. Due to the coexistence of two metal elements, bimetallic selenides can form more active sites, which are conducive to the progress of catalytic reactions. The flame retardant is a multi-level flame-retardant nanostructure obtained by in-situ growth of bimetallic selenides on the surface of modified boron nitride.

[0013] Further optimized, the buffer solution is one or more of tris(hydroxymethylaminomethane) / hydrochloric acid buffer solution, acetic acid / sodium acetate buffer solution, citrate buffer solution, phosphate buffer solution, glycine / hydrochloric acid buffer solution, and tartaric acid / sodium tartrate buffer solution.

[0014] The metal salt is two of sodium molybdate, calcium molybdate, zinc molybdate, cobalt sulfate, cobalt nitrate, cobalt acetate, cobalt chloride, nickel nitrate, nickel acetate, nickel chloride, ferric nitrate, ferric acetate, ferric chloride, copper nitrate, copper acetate, and copper chloride.

[0015] Further optimization, in step 2, the primary product is washed 3 times with distilled water and 2 times with ethanol; after washing, the primary product is dried in a vacuum oven at 50-70° C. for 12-48 hours to obtain the final product P@BN-BMSe powder.

[0016] The preparation method of the flame retardant thermoplastic polyurethane composite material, based on the nano flame retardant P@BN-BMSe prepared above, specifically comprises the following steps: Step 1: Place the nano flame retardant P@BN-BMSe in an organic solvent, stir it ultrasonically for 2-8 h, then add the thermoplastic polyurethane elastomer rubber, heat it to 45-65 °C, and keep stirring for 3-8 h to obtain a composite solution; Step 2: Add the composite solution into deionized water, and after the composite material is precipitated, dry it at 70-100°C for 48-96 hours, and knead and press it at 180-190°C to obtain the preparation of a flame-retardant thermoplastic polyurethane composite material.

[0017] Further optimization, the addition amount of the nano flame retardant P@BN-BMSe is 2wt% of the total mass of the nano flame retardant P@BN-BMSe and the thermoplastic polyurethane elastomer rubber after mixing.

[0018] Further optimization, the organic solvent is one or more of tetrahydrofuran, acetone, N, N-dimethylformamide, N, N-dimethylacetamide, and 1, 4-dioxane.

[0019] Analysis of the principles and improvements of the present invention: The in-situ grown bimetallic selenides on modified boron nitride nanosheets have good catalytic properties and are generally used in electrocatalysis. If used as a flame retardant, its flame retardant properties also need to be considered. Based on the existing bimetallic selenides grown in-situ on boron nitride nanosheets, if they are directly used as flame retardants, there will be problems of poor dispersibility and low flame retardant efficiency. This application is based on existing materials and combines modified boron nitride nanosheets and bimetallic selenides through interface engineering strategies to obtain a new flame retardant, which exerts the synergistic flame retardant effects of physical barrier, free radical capture and catalytic carbonization, significantly improves the flame retardant properties of the material, and reduces the generation of toxic and harmful smoke. Specific improvements include the following points: 1. During the synthesis process, boron nitride has almost no other functional groups except for trace amounts of -OH and -NH2 groups remaining on the edges, so it is very easy to form agglomerations in the matrix. The present invention places boron nitride powder and a modifier in a high-energy ball mill, carries out synchronous exfoliation and modification, and obtains boron nitride nanosheets. Then, a polydopamine modified layer is formed on the surface of boron nitride through a release design strategy. The modified layer has abundant amine groups and can effectively form a chelate structure with metal ions.

[0020] 2. Bimetallic selenides are obtained by using a milder hydrothermal selenization reaction rather than a high-temperature selenization reaction, so that the bimetallic selenides have more defects, and the presence of defects helps to improve the catalytic activity of the nano flame retardant. The flame retardant catalysis of the nano flame retardant here is different from electrocatalysis. The specific process is: promoting the condensation, polymerization, and aromatization reactions of the pyrolysis products of the polymer matrix material, and catalyzing the formation of a cross-linked carbon layer. The carbon layer can block the diffusion and transmission of external heat and cracking products, further improving the flame retardant effect.

[0021] Therefore, the nano flame retardant prepared in this application can be used for flame retardant modification of TPU to promote the cross-linking carbonization process during the combustion of the polymer and generate more protective carbon layers; compared with single metal selenides, bimetallic selenides have more abundant redox reaction sites and phase interfaces. There are abundant lattice defects, heterogeneous electronic states, etc. at the phase interface, which makes the material have more abundant catalytic sites and is conducive to cross-linking carbonization.

[0022] 3. In the flame-retardant TPU composite material prepared by the present invention, during the combustion process, the metal selenide will be converted into metal oxide, and the metal oxide has chemical catalysis and Lewis acid properties, which promotes carbonization.

[0023] The beneficial effects of the present invention are as follows: The bimetallic selenide / modified boron nitride nano flame retardant prepared by the invention has the advantage of high flame retardant efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a scanning electron microscope image of BN in Example 1; Figure 2 This is a scanning electron microscope image of the intermediate product P@BN prepared from the nano flame retardant in Example 1; Figure 3 This is a scanning electron microscope image of the nano flame retardant P@BN-BMSe prepared in Example 1; Figure 4 This is a transmission electron microscope image of the nano flame retardant P@BN-BMSe prepared in Example 1; Figure 5 This is a transmission electron microscope image of the nano flame retardant P@BN-BMSe prepared in Example 2; Figure 6 This is a transmission electron microscope image of the nano flame retardant P@BN-BMSe prepared in Example 3; Figure 7 is the heat release rate curve of commercially available TPU and prepared flame-retardant TPU; Figure 8 It is the total heat release curve of commercially available TPU and prepared flame-retardant TPU; Fig. 9 It is the smoke generation rate curve of commercially available TPU and prepared flame-retardant TPU; Fig.10 is the CO release rate curve of commercially available TPU and the prepared flame-retardant TPU; Fig.11 It is the TG-IR curve of the hydroxyl product of commercial TPU and the prepared flame retardant TPU; Fig.12 It is the TG-IR curve of the ester product of commercial TPU and the prepared flame-retardant TPU; Fig.13 It is the TG-IR curve of aromatic compounds of commercial TPU and prepared flame-retardant TPU; Fig.14 It is the TG-IR curve of the ether compound product of commercial TPU and the prepared flame-retardant TPU; Fig.15It is the TG-IR curve of the aromatic ether product of commercial TPU and the prepared flame-retardant TPU; Fig.16 It is the TG-IR curve of hydrogen cyanide products of commercial TPU and prepared flame retardant TPU; Fig.17 These are the test results of tensile strength and elongation at break of commercially available TPU and the prepared flame-retardant TPU. DETAILED DESCRIPTION

[0025] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. Based on the examples in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0026] Meanwhile, the raw materials or reagents mentioned below that are not described in detail are all commercially available products, and the process steps or methods that are not described in detail are all process steps or methods known to those skilled in the art.

[0027] The sources of some raw materials and reagents involved in the following embodiments and test examples are as follows: Tris / hydrochloric acid buffer was purchased from Sinopharm Chemical Reagent Co., Ltd.; Citrate buffer, Shanghai MacLean Biochemical Technology Co., Ltd.; Glycine / HCl buffer, Shanghai MacLean Biochemical Technology Co., Ltd.; Dopamine hydrochloride was purchased from Tianjin Xiensiopude Technology Co., Ltd.; Sodium molybdate dihydrate was purchased from Sinopharm Chemical Reagent Co., Ltd.; Magnesium molybdate, Shanghai Bailingwei Chemical Technology Co., Ltd.; Calcium molybdate, Shanghai Bailingwei Chemical Technology Co., Ltd.; Selenium powder was purchased from Sinopharm Chemical Reagent Co., Ltd.; Hydrazine hydrate was purchased from Sinopharm Chemical Reagent Co., Ltd.; N,N-dimethylformamide was purchased from Sinopharm Chemical Reagent Co., Ltd.; The TPU was polyester type 85E85, purchased from Baoding Bangtai Polymer New Materials Co., Ltd. Embodiment 1:

[0028] This Example 1 is a specific preparation process of the P@BN-BMSe powder of the present invention: first, 5g of boron nitride and 0.5g of urea are placed in a high-energy ball mill and ball-milled at a speed of 1600rpm for 12h to obtain exfoliated boron nitride. Figure 1 The figure shows an electron microscope image of the exfoliated boron nitride. It can be seen that the BN layer has a clear outline and a smooth surface. Take 1g of exfoliated boron nitride and disperse it in deionized water. Ultrasonicate for 4h to obtain a uniform solution. Add 400ml of tris(hydroxymethyl)aminomethane / hydrochloric acid buffer solution. After ultrasonication for 1h, weigh 0.4g of dopamine hydrochloride and add it to the solution. Stir magnetically at room temperature for 6h. After the reaction is completed, filter to obtain the product. Wash with deionized water until the pH is neutral. Dry at 70 degrees and collect. The product is modified boron nitride P@BN. Figure 2 As shown, this is an electron microscope image of P@BN. The doped boron nitride is blocky and has a rough surface.

[0029] Take 0.5g P@BN and disperse it in deionized water, add 0.75g sodium molybdate and 0.75g cobalt nitrate, and continue to maintain ultrasonic stirring for 1h; at the same time, take 0.5g Se powder and place it in 5ml hydrazine hydrate solution, keep stirring for 1h, add Se solution to P@BN solution, and continue to maintain ultrasonic stirring for 1h; then hydrothermal reaction at 200 degrees for 24h, cool and centrifuge, wash with deionized water 3 times, ethanol wash twice, and finally dry in a vacuum oven for 24h to obtain P@BN-BMSe-1 powder.

[0030] like Figure 3 , which is an electron microscope image of the nano flame retardant P@BN-BMSe-1 prepared in this example, it can be seen that flower-shaped selenide nanosheets grow on the doped P@BN. Figure 4 This is a transmission electron microscope image of the nano flame retardant P@BN-BMSe prepared in this example. The TEM image further illustrates the uniform distribution of the flower-like nanosheets. Embodiment 2:

[0031] This Example 2 is a specific preparation process of the P@BN-BMSe powder described in the present invention: first, 5 g of boron nitride and 1 g of melamine are placed in a high-energy ball mill and ball-milled at a speed of 1400 rpm for 16 hours to obtain modified boron nitride.

[0032] Take 1g of modified boron nitride and disperse it in deionized water, ultrasonicate for 4h to obtain a uniform solution, then add 400ml of citrate buffer solution, ultrasonicate for 1h, weigh 0.2g of dopamine hydrochloride and add it to the solution, magnetically stir at room temperature for 6h, after the reaction is completed, filter to obtain the product, wash with deionized water until the pH is neutral, dry at 50℃ and collect, which is the product P@BN; Take 0.5g P@BN and disperse it in deionized water, add 1.6g cobalt nitrate and 1.6g nickel nitrate, and continue to maintain ultrasonic stirring for 1h; at the same time, take 1.3g Se powder and put it in 10ml hydrazine hydrate solution, keep stirring for 1h, add Se solution to P@BN solution, and continue to maintain ultrasonic stirring for 1h; then hydrothermal reaction at 200 degrees for 24h, cool and centrifuge, wash with deionized water 3 times, ethanol wash twice, and finally dry in a vacuum oven for 24h to obtain P@BN-BMSe-2 powder. Figure 5 This is a transmission electron microscope image of the nano flame retardant P@BN-BMSe prepared in this example. Embodiment 3:

[0033] This Example 3 is a specific preparation process of the P@BN-BMSe powder of the present invention: 5 g of boron nitride and 0.3 g of hexamethylenetetramine are placed in a high-energy ball mill and ball-milled at a speed of 1200 rpm for 20 hours to obtain modified boron nitride.

[0034] Take 1g of modified boron nitride and disperse it in deionized water, ultrasonicate for 4 hours to obtain a uniform solution, add 400ml of glycine / hydrochloric acid buffer solution, ultrasonicate for 1h, then weigh 0.2g of dopamine hydrochloride and add it to the solution, magnetically stir at room temperature for 6h, after the reaction is completed, dry to obtain the product, wash with deionized water until the pH is neutral, dry at 60℃ and collect, which is the product P@BN; Take 0.5g P@BN and disperse it in deionized water, add 2.5g ferric chloride and 2.5g copper nitrate, and continue to maintain ultrasonic stirring for 2h; at the same time, take 2.5g Se powder and place it in 15ml hydrazine hydrate solution, keep stirring for 1h, add Se solution to P@BN solution, and continue to maintain ultrasonic stirring for 1h; then hydrothermal reaction at 200 degrees for 24h, cool and centrifuge, wash with deionized water 3 times, ethanol wash twice, and finally dry in a vacuum oven for 24h to obtain P@BN-BMSe-3 powder. Figure 6 This is a transmission electron microscope image of the nano flame retardant P@BN-BMSe prepared in this example. Embodiment 4:

[0035] The preparation method of the flame-retardant thermoplastic polyurethane composite material comprises: step 1: taking 2g of P@BN-BMSe-1 prepared according to the method described in Example 1, dispersing it in 100ml N,N-dimethylformamide (DMF) by ultrasonic stirring for 2 hours, then adding 98g of TPU masterbatch, and continuing ultrasonic stirring for 4h to completely dissolve the polyurethane elastomer. Step 2: slowly dripping the solution obtained in step 1 into deionized water to obtain a precipitate, taking out the precipitate, and squeezing out the water. Then drying in an oven at 100°C (72h). Afterwards, the composite is pressed into a shape of 100*100*3mm using a plate press to obtain a flame-retardant thermoplastic polyurethane composite material TPU / 2.0P@BN-BMSe-1 with an addition amount of 2%. Embodiment 5:

[0036] 2 g of P@BN-BMSe-2 prepared according to the method described in Example 2 was taken, and a flame-retardant thermoplastic polyurethane composite material with an addition amount of 2% was prepared according to the same method as Example 4, TPU / 2.0P@BN-BMSe-2. Embodiment 6:

[0037] 2 g of P@BN-BMSe-3 prepared according to the method described in Example 3 was taken, and a flame-retardant thermoplastic polyurethane composite material with an addition amount of 2% was prepared according to the same method as Example 4, which was recorded as TPU / 2.0P@BN-BMSe-3.

[0038] Test Example 1: Cone calorimetry test of commercially available TPU and flame-retardant TPU prepared in Examples 4, 5, and 6 The specific test process is as follows: According to ISO 5660 standard, a cone calorimeter (UK, Fire Testing Technology) was used to perform a combustion test on the samples. The specific samples were commercially available TPU and the flame-retardant TPU prepared in Examples 4, 5, and 6. The sample specifications were 100×100×3mm 3 , using electric spark ignition, heat radiation flux of 35 kW / m 2 , the heat release curve is calculated based on the oxygen consumption principle, and parameters such as smoke release rate and specific extinction area are monitored simultaneously. Figure 7 The heat release rate curve is shown; Figure 8 The total heat release curve is shown; Fig. 9 The smoke production rate curve is shown; Fig.10 Specific extinction area curves are shown.

[0039] It can be seen that the peak heat release rate, total heat release, smoke release rate and CO release rate of pure TPU are 1236.5 kW / m 2 、87.1 MJ / m 2 、0.159 m2 / s and 0.0135g / s. After adding 2.0wt% flame retardant, the peak heat release rate and total heat release of TPU decreased. Among them, after adding P@BN-BMSe-2, the peak heat release rate and total heat release decreased by 51.9% and 33.4%, respectively. The peak smoke release rate and CO release rate decreased by 45.8% and 43.8%, respectively, indicating that P@BN-BMSe-2 can significantly inhibit the release of heat and toxic smoke during the combustion of TPU. The flame retardant effect of P@BN-BMSe-2 is better than that of P@BN-BMSe-1 and P@BN-BMSe-3. Too much BMSe will enhance the catalytic degradation of the particles and aggravate the cracking of the polymer. Too little BMSe will weaken the catalytic carbonization of the particles, which is not conducive to the formation of a protective carbon layer.

[0040] Test Example 2: Thermogravimetric infrared TG-IR test of commercially available TPU and flame-retardant TPU prepared in Examples 4, 5, and 6 The specific test process is as follows: Nicolet 6700 FTIR spectrophotometer is used in conjunction with TGA Q5000 thermogravimetric analyzer to obtain TGIR results. The test atmosphere is nitrogen and the heating rate is 20°C / min. The sampling mass of the commercially available TPU and the flame-retardant TPU prepared in Examples 4, 5, and 6 is about 10 mg. After thermogravimetry and infrared are combined, the gas components decomposed during the thermal weight loss process of the sample under programmed temperature control are transmitted to the infrared gas detection cell through a constant temperature delivery pipe, and the escaping gas is qualitatively and quantitatively analyzed respectively.

[0041] Fig.11 It is the test result of hydroxyl products. After adding 2.0wt% P@BN-BMSe-1, P@BN-BMSe-2, and P@BN-BMSe-3 flame retardants, the peak absorbance decreased by 17.1%, 24.9%, and 24.3%, respectively; Fig.12 It is the test result of ester products. After adding 2.0wt% P@BN-BMSe-1, P@BN-BMSe-2, and P@BN-BMSe-3 flame retardants, the peak absorbance decreased by 11.7%, 33.0%, and 19.1%, respectively; Fig.13 It is the test result of aromatic compounds. After adding 2.0wt% P@BN-BMSe-1, P@BN-BMSe-2, and P@BN-BMSe-3 flame retardants, the peak absorbance decreased by 32.7%, 45.1%, and 33.9%, respectively; Fig.14This is the test result of the ether compound product. After adding 2.0wt% P@BN-BMSe-1, P@BN-BMSe-2, and P@BN-BMSe-3 flame retardants, the peak absorbance decreased by 7.7%, 24.8%, and 14.3%, respectively; Fig.15 This is the test result of aromatic ether compound products. After adding 2.0wt% P@BN-BMSe-1, P@BN-BMSe-2, and P@BN-BMSe-3 flame retardants, the peak absorbance decreased by 19.3%, 48.1%, and 31.8%, respectively; Fig.16 This is the test result of hydrogen cyanide product. After adding 2.0wt% P@BN-BMSe-1, P@BN-BMSe-2, and P@BN-BMSe-3 flame retardants, the absorption peaks decreased by 6.3%, 25.1%, and 8.3%, respectively.

[0042] The above results show that the generation of both flammable and toxic gases is inhibited after using P@BN-BMSe, among which P@BN-BMSe-2 has the best inhibition effect.

[0043] Test Example 3 Mechanical tensile properties test of commercially available TPU and flame-retardant TPU prepared in Examples 4, 5, and 6 The specific test process is as follows: the mechanical properties are tested and recorded by a universal tensile tester (CMT4204, China MTS Systems Co., Ltd.). The samples are commercially available TPU and the flame-retardant TPU prepared in Examples 4, 5, and 6. Five specimens are tested for each sample and the sample is prepared according to the national standard GB / T 1040. The tensile strength and elongation at break data are obtained by testing.

[0044] like Fig.17 As shown, the flame retardant TPU prepared in Examples 4, 5, and 6 did not reduce the tensile properties due to the addition of flame retardants, and compared with commercially available TPU, after adding 2.0wt% P@BN-BMSe-1, P@BN-BMSe-2, and P@BN-BMSe-3 flame retardants, the tensile strength increased from 31.2MPa to 35.4MPa, 42.1MPa, and 38.2MPa, respectively, and the elongation at break increased from 578.8% to 589.3%, 624.3%, and 314.4%, respectively.

[0045] The undescribed parts involved in the present invention are the same as the prior art or are implemented by using the prior art.

[0046] The above are only preferred embodiments of the present invention, and the present invention is not limited to the contents of the embodiments. For those skilled in the art, various changes and modifications can be made within the scope of the technical solution of the present invention, and any changes and modifications made are within the protection scope of the present invention.

Claims

1. A method for preparing a bimetallic selenide / modified boron nitride nano flame retardant, characterized in that: The steps include: Step 1: Place the modified boron nitride in deionized water and obtain a uniform dispersion solution 1 by ultrasonic treatment; take a buffer solution, add it to the dispersion solution 1, and then weigh dopamine hydrochloride and add it to the mixed solution for reaction; after the reaction is completed, filter to obtain the product, then wash it with deionized water until the pH is neutral, dry it and collect it to obtain P@BN; Step 2: P@BN is dispersed in deionized water, and then mixed metal salts are added and ultrasonically stirred to form dispersion liquid 2; at the same time, selenium powder is placed in a hydrazine hydrate solution and dissolved by magnetic stirring to form a selenium solution; the selenium solution is added to dispersion liquid 2, and ultrasonic stirring is continued before hydrothermal reaction; the initial product after the reaction is centrifuged, washed, and dried in sequence to obtain the final product, nano flame retardant P@BN-BMSe.

2. The method for preparing the bimetallic selenide / modified boron nitride nano flame retardant according to claim 1, characterized in that: In the step 1, the boron nitride and the modifier are placed in a high-energy ball mill for simultaneous stripping and modification to obtain modified boron nitride.

3. The method for preparing the bimetallic selenide / modified boron nitride nano flame retardant according to claim 2, characterized in that: The boron nitride is one of hexagonal boron nitride, rhombohedral boron nitride, cubic boron nitride or wurtzite boron nitride; The modifier is a mixture of one or more of urea, dicyandiamide, melamine and hexamethylenetetramine.

4. The method for preparing the bimetallic selenide / modified boron nitride nano flame retardant according to any one of claims 1 to 3, characterized in that: In step 2, the mass ratio of P@BN to the mixed metal salt is (1:3) to (1:10), and the mixed metal salt is composed of two metal salts, and the mass ratio of the two is 1:

1.

5. The method for preparing the bimetallic selenide / modified boron nitride nano flame retardant according to any one of claim 4, characterized in that: In the step 2, the dosage ratio of the P@BN, selenium powder and hydrazine hydrate is 1 g: (1-5) g: (10-30) ml.

6. The method for preparing the bimetallic selenide / modified boron nitride nano flame retardant according to claim 5, characterized in that: The buffer solution is one or more of tris(hydroxymethylaminomethane) / hydrochloric acid buffer solution, acetic acid / sodium acetate buffer solution, citrate buffer solution, phosphate buffer solution, glycine / hydrochloric acid buffer solution, tartaric acid / sodium tartrate buffer solution; The metal salt is two of sodium molybdate, calcium molybdate, zinc molybdate, cobalt sulfate, cobalt nitrate, cobalt acetate, cobalt chloride, nickel nitrate, nickel acetate, nickel chloride, ferric nitrate, ferric acetate, ferric chloride, copper nitrate, copper acetate, and copper chloride.

7. The method for preparing the bimetallic selenide / modified boron nitride nano flame retardant according to claim 6, characterized in that: In step 2, the primary product is washed 3 times with distilled water and 2 times with ethanol; After washing, the initial product was dried in a vacuum oven at 50-70 °C for 12-48 h to obtain the final product P@BN-BMSe powder.

8. A method for preparing a flame retardant thermoplastic polyurethane composite material, characterized in that: The nano flame retardant P@BN-BMSe prepared according to any one of claims 1 to 7 specifically comprises the following steps: Step 1: Place the nano flame retardant P@BN-BMSe in an organic solvent, stir it ultrasonically for 2-8 h, then add the thermoplastic polyurethane elastomer rubber, heat it to 45-65 °C, and keep stirring for 3-8 h to obtain a composite solution; Step 2: Add the composite solution into deionized water, and after the composite material is precipitated, dry it at 70-100°C for 48-96 hours, and knead and press it at 180-190°C to obtain the preparation of a flame-retardant thermoplastic polyurethane composite material.

9. The method for preparing the flame-retardant thermoplastic polyurethane composite material according to claim 8, characterized in that: The amount of the nano flame retardant P@BN-BMSe added is 2wt% of the total mass of the nano flame retardant P@BN-BMSe and the thermoplastic polyurethane elastomer rubber after mixing.

10. The method for preparing the flame-retardant thermoplastic polyurethane composite material according to claim 9, characterized in that: The organic solvent is one or more of tetrahydrofuran, acetone, N, N-dimethylformamide, N, N-dimethylacetamide, and 1,4-dioxane.

Citation Information

Patent Citations

  • A kind of montmorillonite composite flame retardant and preparation method thereof

    CN105175786B

  • A low-smoke thermoplastic polyurethane elastomer composite material and its preparation method

    CN111607219B

  • A halogen-free flame-retardant thermoplastic polyurethane nanocomposite material and its preparation method

    CN111849145B

  • Nano flame retardant and flame-retardant thermoplastic polyurethane composite material

    CN116535737A

  • Polyion liquid / boron nitride nanosheet composite flame retardant as well as preparation method and application thereof

    CN117247601A